Pragmatic effect of an essential oil mouthwash as an adjunct to scaling on bacterial growth and gingival inflammation: A randomized controlled study - Banda Madhavi; Jammula Surya Prasanna (Wolters Kluwer Medknow Publications, 2020)
Background: Dental plaque, comprehend of microorganisms which are considered as a main etiological factor for gingivitis, is the mildest form of periodontal diseases. This burden can be reduced by scaling, but additive effects can be achieved using mouthwashes as an adjunct. Aims: To assess the clinical efficacy of essential oil (EO) mouthwash containing a combination of peppermint oil and tea tree oil on the reduction of bacterial plaque, gingivitis, as well as the colony forming units (CFU) before and after scaling. Materials and Methods: This double-blind randomized clinical trial contains thirty subjects with severe gingivitis. All were divided into three groups, A, B and C, each group contains ten patients. Baseline plaque samples were collected for microbiological evaluation from all the subjects, and plaque index (PI) and gingival index (GI) were recorded. Patients in Group A have been prescribed 10 ml of freshly prepared mouthwash after scaling thrice a day for 3 weeks; patients in Group B underwent scaling only. Patients in Group C have been prescribed only 10 ml of mouthwash without scaling. After 3 weeks, plaque samples were collected to reevaluate PI, GI, and CFU from all the samples. Statistical Analysis: One-way analysis of variance and paired sample t-test were used for analysis. Results: Reduction was seen in PI, GI and CFU in Groups A and B when compared to Group C, and there was also a significant reduction seen in Group A when compared to Group B, when P < 0.05 was considered significant. Conclusions: EO mouthwash was effective in the treatment of plaque-induced gingivitis as an adjunct to scaling without any side effects.